The professional design guide to green roofs - Dakin, Karla; Benjamin, Lisa Lee.; Pantiel, Mindy (Portland, Or. : Timber Press, 2013)
Through the author's words and gorgeous photography, this book provides sound counsel for all phases of a green roof project, from pre-design through construction and often-neglected maintenance. It also transcends previous green roof books by offering chapters of thoughtful design inspiration.--COVER.
Sources of inspiration -- Shapes and patterns -- Creating living spaces -- Wildlife friendly spaces -- Plant-driven environments -- The predesign phase -- Site analysis -- Program -- Master planning and conceptual design -- Design development and construction documents -- Contracts, construction, and maintenance -- The evolving frontier of landscape design.
Includes bibliographical references and index.
Keywords: Green roofs (Gardening) -- Design and construction